Preparation method of antioxidant antibacterial chitosan composite material

By grafting silybin into a chitosan matrix with an acyl chloride crosslinking agent and quaternization, the composite material achieves improved antibacterial and antioxidant properties, addressing limitations of existing chitosan materials.

CN119174836AInactive Publication Date: 2024-12-24HAERBIN FUERSITE BIOLOGY ENG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411696833.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing chitosan materials lack effective antibacterial and antioxidant properties, limiting their applications in medical and cosmetic products.

Method used

A method involving the preparation of a chitosan composite material by grafting silybin into a chitosan matrix using an acyl chloride crosslinking agent, followed by quaternization with alkyl chlorides to introduce antibacterial quaternary ammonium salt groups and antioxidant flavonoids.

Benefits of technology

The resulting composite material exhibits enhanced antibacterial performance against Staphylococcus aureus, Escherichia coli, and Candida albicans, and excellent DPPH and ABTS free radical scavenging rates, making it suitable for antibacterial and antioxidant dressings and masks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119174836A_ABST
    Figure CN119174836A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chitosan, and discloses a preparation method of an antioxidant antibacterial chitosan composite material. According to the preparation method, an acyl chloride cross-linking agent is utilized to react with chitosan and silibinin respectively, and then the acyl chloride cross-linking agent and alkyl chloride are subjected to quaternization reaction, so that the antioxidant and antibacterial chitosan composite material is obtained. A large number of antibacterial quaternary ammonium salt groups are introduced into the chitosan composite material, so that the antibacterial performance of the composite material on staphylococcus aureus, escherichia coli and candida albicans is remarkably improved. Meanwhile, a natural flavonoid compound silybin with antioxidant activity is grafted into a chitosan matrix, so that the material is endowed with excellent DPPH free radical and ABTS < + >. Free radical scavenging rate, and the material shows good free radical oxidation resistance. The problem that the chitosan material is poor in antibacterial and anti-oxidation performance is solved, and the chitosan material has better practical application in antibacterial and anti-oxidation application dressings, gauze bandages, masks and other materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chitosan, in particular to a method for preparing an antioxidant and antibacterial chitosan composite material. Background Art

[0002] Chitosan is a natural polysaccharide derivative that is cheap, easy to obtain, green and environmentally friendly, has good biocompatibility, and has certain antibacterial properties. It is widely used in antibacterial and anti-inflammatory dressings, hemostatic dressings, anti-free radical oxidation films, anti-aging masks, etc. Superoxide radicals and linoleic acid free radicals have strong zinc oxide, which can cause great harm to human functions and induce aging, arteriosclerosis and other diseases. The development of new antioxidant bioactive materials is a research hotspot.

[0003] Silybin is a natural flavonoid antioxidant extracted from milk thistle plants. It is non-toxic and non-irritating and has broad application prospects in the fields of anti-oxidation, anti-aging, biomedicine, etc. The Chinese patent with publication number CN117205766A discloses a blood purification membrane for intervening oxidative stress without adding a small molecule modifier and a preparation method thereof. Silybin is grafted onto the surface of a polysulfone membrane to form an antioxidant functional layer. The obtained blood purification membrane has excellent free radical scavenging rate and antioxidant properties. Compared with the invention, the present invention grafts silybin into a chitosan matrix, and the obtained chitosan composite material has better antibacterial and anti-free radical oxidation properties. Summary of the invention

[0004] (I) Technical problems to be solved: In view of the deficiencies of the prior art, the present invention provides a chitosan composite material with antioxidant and antibacterial effects.

[0005] (II) Technical solution: A method for preparing an antioxidant and antibacterial chitosan composite material: S1. Add 1.5-2% acetic acid solution and 100 parts by weight of chitosan into a reaction bottle, stir and dissolve, then add tetrahydrofuran, 6-25 parts by weight of acyl chloride crosslinking agent, 15-40 parts by weight of silybin, and 3.4-9.2 parts by weight of triethylamine. After the reaction is completed, add sodium hydroxide solution dropwise, adjust the pH of the reaction solution to 7-7.5, distill under reduced pressure, filter, wash with water, ethanol, and dry to obtain silybin-modified chitosan.

[0006] S2. Add N,N-dimethylformamide and 100 parts by weight of silybin modified chitosan into a reaction bottle, add 4-20 parts by weight of alkyl chloride after stirring, pour the solution on the surface of a glass plate after the reaction, cast it into a film, dry it to remove the solvent, wash it with dichloromethane and ethanol in turn, then soak the film in distilled water, take out the film material and dry it to obtain an antioxidant and antibacterial chitosan composite material.

[0007] Preferably, the reaction temperature in S1 is 20-30°C and the reaction time is 12-18h.

[0008] Preferably, the reaction temperature in S2 is 100-130° C., and the reaction time is 36-48 h.

[0009] Preferably, the alkyl chloride in S2 is any one of 1-chlorododecane, 1-chlorotridecane, 1-chlorotetradecane, 1-chloropentadecane or 1-chlorohexadecane.

[0010] Preferably, the preparation method of the acyl chloride cross-linking agent is: (1) Add ethanol, 100 parts by weight of terephthalaldehyde, and 220-242 parts by weight of N,N-bis(2-hydroxyethyl)ethylenediamine to a reaction bottle, heat to 40-50°C, react for 6-8 hours, distill under reduced pressure, wash with petroleum ether, and dry to obtain an intermediate.

[0011] (2) Add dichloromethane, 100 parts by weight of the intermediate, 140-168 parts by weight of succinic anhydride, and 108-130 parts by weight of 4-dimethylaminopyridine to a reaction flask, carry out esterification reaction at 25-40°C for 3-8 hours, distill under reduced pressure, wash with petroleum ether, add the product to thionyl chloride, heat to 60-70°C, carry out acyl chloride reaction for 3-5 hours, distill under reduced pressure, and dry to obtain an acyl chloride crosslinking agent.

[0012] (III) Technical effect: The present invention uses terephthalaldehyde, N,N-bis(2-hydroxyethyl)ethylenediamine, succinic anhydride and thionyl chloride as reactants to prepare an acyl chloride crosslinking agent containing a tertiary amine group. The multiple acyl chloride groups are used to react with the active amino and hydroxymethyl groups of chitosan and the active hydroxymethyl groups of silybin, and finally the introduced tertiary amine groups react with alkyl chlorides such as 1-chlorotetradecane to undergo quaternization reaction, and then cast into a film to obtain an antioxidant and antibacterial chitosan composite material.

[0013] The present invention introduces a large number of antibacterial quaternary ammonium salt groups into the chitosan composite material, which significantly improves the antibacterial performance of the composite material against Staphylococcus aureus, Escherichia coli, and Candida albicans. At the same time, the natural flavonoid compound silybin with antioxidant activity is grafted into the chitosan matrix, giving the material excellent DPPH free radical and ABTS + ·Free radical scavenging rate, showing good anti-free radical oxidation performance. This makes chitosan materials have better practical applications in antibacterial and antioxidant dressings, gauze bandages, facial masks and other materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is the reaction formula for preparing acyl chloride cross-linking agent.

[0015] Figure 2It is the reaction formula of the antioxidant and antibacterial chitosan composite material. DETAILED DESCRIPTION

[0016] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.

[0017] Example 1 (1) Add 80 mL of ethanol, 3 g of terephthalaldehyde, and 6.93 g of N,N-bis(2-hydroxyethyl)ethylenediamine to a reaction bottle, heat to 50°C, react for 6 h, distill under reduced pressure, wash with petroleum ether, and dry to obtain an intermediate.

[0018] (2) Add 80 mL of dichloromethane, 2 g of the intermediate, 2.8 g of succinic anhydride, and 2.16 g of 4-dimethylaminopyridine to a reaction bottle, carry out esterification reaction at 30°C for 5 h, distill under reduced pressure, wash with petroleum ether, add the product to 40 mL of thionyl chloride, heat to 60°C, carry out chlorination reaction for 4 h, distill under reduced pressure, and dry to obtain an acyl chloride crosslinking agent.

[0019] (3) Add 200 mL of 2% acetic acid solution and 50 g of chitosan to the reaction bottle, stir and dissolve, then add 200 mL of tetrahydrofuran, 3 g of acyl chloride crosslinking agent, 7.5 g of silybin, and 1.7 g of triethylamine, react at 25 °C for 12 h, add sodium hydroxide solution dropwise, adjust the pH of the reaction solution to 7.5, distill under reduced pressure, filter, wash with water, ethanol, and dry to obtain silybin-modified chitosan.

[0020] (4) Add 500 mL of N,N-dimethylformamide and 50 g of silybin modified chitosan into a reaction bottle, stir and then add 2 g of 1-chlorotetradecane, heat to 130 °C, react for 36 h, pour the solution onto the surface of a glass plate, cast into a film, dry to remove the solvent, wash with dichloromethane and ethanol in turn, then soak the film in distilled water, take out the film material and dry it to obtain an antioxidant and antibacterial chitosan composite material.

[0021] Example 2 (1) Add 90 mL of ethanol, 3 g of terephthalaldehyde, and 7.26 g of N,N-bis(2-hydroxyethyl)ethylenediamine to a reaction bottle, heat to 40°C, react for 8 hours, distill under reduced pressure, wash with petroleum ether, and dry to obtain an intermediate.

[0022] (2) Add 120 mL of dichloromethane, 2 g of the intermediate, 3.36 g of succinic anhydride, and 2.6 g of 4-dimethylaminopyridine to a reaction flask, carry out esterification reaction at 40°C for 3 h, distill under reduced pressure, wash with petroleum ether, add the product to 30 mL of thionyl chloride, heat to 60°C, carry out chlorination reaction for 5 h, distill under reduced pressure, and dry to obtain an acyl chloride crosslinking agent.

[0023] (3) Add 200 mL of 2% acetic acid solution and 50 g of chitosan to the reaction bottle, stir to dissolve, then add 250 mL of tetrahydrofuran, 7.8 g of acyl chloride crosslinking agent, 14 g of silybin, and 3.2 g of triethylamine, react at 20 ° C for 18 h, add sodium hydroxide solution dropwise, adjust the pH of the reaction solution to 7, distill under reduced pressure, filter, wash with water, ethanol, and dry to obtain silybin-modified chitosan.

[0024] (4) Add 600 mL of N,N-dimethylformamide and 50 g of silybin modified chitosan into the reaction bottle, stir and then add 6 g of 1-chlorohexadecane, heat to 100 °C, react for 48 h, pour the solution on the surface of a glass plate, cast into a film, dry to remove the solvent, wash with dichloromethane and ethanol in turn, then soak the film in distilled water, take out the film material and dry it to obtain an antioxidant and antibacterial chitosan composite material.

[0025] Example 3 (1) Add 80 mL of ethanol, 3 g of terephthalaldehyde, and 6.6 g of N,N-bis(2-hydroxyethyl)ethylenediamine to a reaction bottle, heat to 50°C, react for 6 h, distill under reduced pressure, wash with petroleum ether, and dry to obtain an intermediate.

[0026] (2) Add 100 mL of dichloromethane, 2 g of the intermediate, 3.36 g of succinic anhydride, and 2.45 g of 4-dimethylaminopyridine to a reaction flask, carry out esterification reaction at 25°C for 8 h, distill under reduced pressure, wash with petroleum ether, add the product to 40 mL of thionyl chloride, heat to 70°C, carry out chlorination reaction for 3 h, distill under reduced pressure, and dry to obtain an acyl chloride crosslinking agent.

[0027] (3) Add 250 mL of 1.5% acetic acid solution and 50 g of chitosan to the reaction bottle, stir and dissolve, then add 300 mL of tetrahydrofuran, 12.5 g of acyl chloride crosslinking agent, 20 g of silybin, and 4.6 g of triethylamine, react at 30 ° C for 12 h, add sodium hydroxide solution dropwise, adjust the pH of the reaction solution to 7, distill under reduced pressure, filter, wash with water, ethanol, and dry to obtain silybin-modified chitosan.

[0028] (4) Add 800 mL of N,N-dimethylformamide and 50 g of silybin modified chitosan into the reaction bottle, stir and add 10 g of 1-chlorododecane, heat to 120 °C, react for 36 h, pour the solution on the surface of a glass plate, cast into a film, dry to remove the solvent, wash with dichloromethane and ethanol in turn, then soak the film in distilled water, take out the film material and dry it to obtain an antioxidant and antibacterial chitosan composite material.

[0029] Comparative Example 1 (1) Add 200 mL of 2% acetic acid solution and 50 g of chitosan to a reaction bottle, stir and dissolve, then add 200 mL of tetrahydrofuran, 3 g of acyl chloride crosslinking agent (prepared in the same manner as in Example 1), 7.5 g of silybin, and 1.7 g of triethylamine, react at 25° C. for 12 h, add sodium hydroxide solution dropwise, adjust the pH of the reaction solution to 7.5, distill under reduced pressure, filter, wash with water, ethanol, and dry to obtain silybin-modified chitosan.

[0030] (2) Add 500 mL of N,N-dimethylformamide and 50 g of silybin modified chitosan into a reaction bottle, stir and pour the solution onto a glass plate to form a film, dry and remove the solvent, wash with dichloromethane and ethanol in turn, then soak the film in distilled water, take out the film material and dry it to obtain an antioxidant and antibacterial chitosan composite material.

[0031] Comparative Example 2 (1) Add 200 mL of 2% acetic acid solution and 50 g of chitosan to a reaction bottle, stir and dissolve, then add 200 mL of tetrahydrofuran, 3 g of acyl chloride crosslinking agent (same as the preparation method in Example 1), and 1.7 g of triethylamine, react at 25°C for 12 h, add sodium hydroxide solution dropwise, adjust the pH of the reaction solution to 7.5, distill under reduced pressure, filter, wash with water, ethanol, and dry to obtain modified chitosan.

[0032] (2) Add 500 mL of N,N-dimethylformamide and 50 g of modified chitosan into the reaction bottle, stir and add 2 g of 1-chlorotetradecane, heat to 130 °C, react for 36 h, pour the solution on the surface of a glass plate, cast into a film, dry to remove the solvent, wash with dichloromethane and ethanol in turn, then soak the film in distilled water, take out the film material and dry it to obtain an antioxidant and antibacterial chitosan composite material.

[0033] Comparative Example 3 (1) Add 200 mL of 2% acetic acid solution and 50 g of chitosan to a reaction bottle, stir and dissolve, then add 200 mL of tetrahydrofuran, 3 g of trimesoyl chloride, 7.5 g of silybin, and 1.7 g of triethylamine, react at 25 °C for 12 h, add sodium hydroxide solution dropwise, adjust the pH of the reaction solution to 7.5, distill under reduced pressure, filter, wash with water, ethanol, and dry in turn to obtain silybin-modified chitosan.

[0034] (2) Add 500 mL of N,N-dimethylformamide and 50 g of silybin modified chitosan into a reaction bottle, stir, then add 2 g of 1-chlorotetradecane, heat to 130 °C, stir for 36 h, pour the solution onto the surface of a glass plate, cast into a film, dry to remove the solvent, wash with dichloromethane and ethanol in turn, then soak the film in distilled water, take out the film material and dry it to obtain an antioxidant and antibacterial chitosan composite material.

[0035] Antibacterial performance test: The antioxidant and antibacterial chitosan composite material was made into a circular membrane material with a diameter of 6 mm. The test bacteria were Staphylococcus aureus, Escherichia coli, and Candida albicans. The test bacteria were activated at 37°C for 24 hours and made into 10 6 cfu / mL of bacterial suspension, then evenly coat 0.1mL of the bacterial suspension on the surface of beef extract peptone agar medium, stick the circular membrane material on the surface of beef extract peptone agar medium, place it in a constant temperature and humidity incubator, culture it at 37℃ for 24h, and then measure the diameter of the inhibition zone.

[0036] Table 1

[0037] As can be seen from Table 1, the antibacterial zone diameters of the antioxidant and antibacterial chitosan composite materials of Examples 1-3 against Staphylococcus aureus, Escherichia coli, and Candida albicans are very high, and the antibacterial properties are very good. This is because chitosan and silybin are reacted with an acyl chloride cross-linking agent containing multiple tertiary amine groups to obtain silybin-modified chitosan containing a large number of tertiary amine groups, and then the tertiary amine groups are quaternized with alkyl chlorides such as 1-chlorotetradecane to obtain chitosan composite materials containing a large number of antibacterial quaternary ammonium salt groups, which significantly improves the antibacterial properties of the composite materials.

[0038] Comparative Example 2: Chitosan is reacted with an acyl chloride crosslinking agent and 1-chlorotetradecane in sequence, and the obtained chitosan composite material also contains a large amount of antibacterial quaternary ammonium salt groups, has a high inhibition zone diameter, and has good antibacterial properties.

[0039] The anti-oxidative and antibacterial chitosan composite materials of Comparative Examples 1 and 3 have low inhibition zone diameters against Staphylococcus aureus, Escherichia coli, and Candida albicans, and have poor antibacterial properties. This is because the silybin-modified chitosan in Comparative Example 1 does not undergo quaternization reaction with alkyl chloride, and the obtained chitosan composite material does not contain antibacterial quaternary ammonium salt groups, resulting in poor antibacterial properties of the material. Comparative Example 3 uses trimesoyl chloride to react with chitosan, and the obtained silybin-modified chitosan does not contain tertiary amine groups, and cannot undergo quaternization reaction with 1-chlorotetradecane. The obtained chitosan composite material does not contain antibacterial quaternary ammonium salt groups, resulting in poor antibacterial properties of the material.

[0040] Antioxidant performance test: Prepare an aqueous solution of 1,1-diphenyl-2-trinitrophenylhydrazine DPPH with a concentration of 0.1mmol / L, and add a circular membrane of antioxidant and antibacterial chitosan composite material with a diameter of 4cm to the DPPH solution as the experimental group. The blank group is a DPPH solution without antioxidant and antibacterial chitosan composite material. After mixing, place it away from light for 2 hours, take the supernatant, test the absorbance at 517nm by enzyme label analyzer, and calculate the DPPH free radical scavenging rate R. R=(A-A1) / A×100%. A is the absorbance of the blank group. A1 is the absorbance of the experimental group.

[0041] Prepare a mixed aqueous solution of 5mmol / L 2'-hydrazine-bis-3-ethylbenzothiazoline-6-sulfonic acid ABTS and 1.75mmol / L potassium persulfate, and react for 12h in the dark to prepare ABTS. + · Free radical solution. Test the absorbance at 734 nm, then add ethanol to dilute, control the absorbance of the solution to 0.70, add a 4 cm diameter circular membrane of antioxidant and antibacterial chitosan composite material as the experimental group. The blank group is not added with antioxidant and antibacterial chitosan composite material, and is placed in the dark for 1 hour. Take the supernatant, test the absorbance at 734 nm in the dark, and calculate the ABTS + · Free radical scavenging rate R. R = (A-A1) / A×100%. A is the absorbance of the blank group. A1 is the absorbance of the experimental group.

[0042] Table 2

[0043] As shown in Table 1, the antioxidant and antibacterial chitosan composite materials of Examples 1-3 have high DPPH free radical scavenging rates and ABTS + · Free radical scavenging rate, showing good antioxidant properties, this is because the natural flavonoid compound silybin with antioxidant activity is grafted into the chitosan matrix using an acyl chloride crosslinker, giving the material excellent free radical scavenging rate and antioxidant activity.

[0044] The chitosan composite materials of Comparative Examples 1 and 3 are also grafted with silybin and have good free radical scavenging rate and antioxidant activity.

[0045] The chitosan composite material of Comparative Example 2 was not grafted with silybin, had a very low free radical scavenging rate, and had poor antioxidant activity.

[0046] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A method for preparing an antioxidant and antibacterial chitosan composite material, characterized in that: The preparation method comprises the following steps: S1, add acetic acid solution and 100 parts by weight of chitosan into a reaction flask, stir and dissolve, add tetrahydrofuran, 6-25 parts by weight of acyl chloride crosslinking agent, 15-40 parts by weight of silybin, and 3.4-9.2 parts by weight of triethylamine, add sodium hydroxide solution dropwise after the reaction is completed, distill under reduced pressure, wash, and dry to obtain silybin-modified chitosan; The structural formula of the acyl chloride cross-linking agent is: ; S2. Add N,N-dimethylformamide and 100 parts by weight of silybin modified chitosan into a reaction bottle, add 4-20 parts by weight of alkyl chloride after stirring, pour the solution on the surface of a glass plate after the reaction, cast it into a film, dry it to remove the solvent, wash it, then soak the film in distilled water, take out the film material and dry it to obtain an antioxidant and antibacterial chitosan composite material.

2. The method for preparing the antioxidant and antibacterial chitosan composite material according to claim 1, characterized in that: The mass fraction of the acetic acid solution in S1 is 1.5-2%.

3. The method for preparing the antioxidant and antibacterial chitosan composite material according to claim 1, characterized in that: The reaction temperature in S1 is 20-30°C and the reaction time is 12-18h.

4. The method for preparing the antioxidant and antibacterial chitosan composite material according to claim 1, characterized in that: In the S1, sodium hydroxide solution is added dropwise to adjust the pH of the reaction solution to 7-7.

5.

5. The method for preparing the antioxidant and antibacterial chitosan composite material according to claim 1, characterized in that: The reaction temperature in S2 is 100-130° C., and the reaction time is 36-48 hours.

6. The method for preparing the antioxidant and antibacterial chitosan composite material according to claim 1, characterized in that: The alkyl chloride in S2 is any one of 1-chlorododecane, 1-chlorotridecane, 1-chlorotetradecane, 1-chloropentadecane or 1-chlorohexadecane.

7. The method for preparing the antioxidant and antibacterial chitosan composite material according to claim 1, characterized in that: The preparation method of the acyl chloride cross-linking agent is: (1) Add ethanol, 100 parts by weight of terephthalaldehyde, and 220-242 parts by weight of N,N-bis(2-hydroxyethyl)ethylenediamine to a reaction bottle, heat to 40-50° C., perform vacuum distillation after the reaction, wash, and dry to obtain an intermediate; (2) Add dichloromethane, 100 parts by weight of the intermediate, 140-168 parts by weight of succinic anhydride, and 108-130 parts by weight of 4-dimethylaminopyridine into a reaction flask to carry out esterification reaction, distill under reduced pressure, wash, add the product to thionyl chloride, carry out acyl chloride reaction, distill under reduced pressure, and dry to obtain an acyl chloride crosslinking agent.

8. The method for preparing the antioxidant and antibacterial chitosan composite material according to claim 7, characterized in that: The reaction temperature in (1) is 40-50°C and the reaction time is 6-8h.

9. The method for preparing the antioxidant and antibacterial chitosan composite material according to claim 7, characterized in that: The temperature of the esterification reaction in (2) is 25-40°C, and the reaction time is 3-8h; the temperature of the acyl chlorination reaction is 60-70°C, and the reaction time is 3-5h.

Citation Information

Patent Citations

  • Preparation method for silymarin chitosan polymer micelles

    CN110934826A

  • Biomass antibacterial composite membrane material and preparation method thereof

    CN115028904A

  • High-adhesion composite sodium hyaluronate repair patch and preparation method thereof

    CN116270255A

  • Medical high-molecular polymer carrier and application thereof as skin protective agent

    CN118496398A